DFT and CBS study of ethyl acetate conformers in the neutral hydrolysis - Vera Khoirunisa,; Rusydi, Febdian; Roichatul Madinah,; Dipojono, Hermawan Kresno; Ahmad, Faozan; Mudasir,; Ira Puspitasari,; Azizan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
First-principles calculations are commonly used to search for possible transition states in reaction kinetics studies, which are such a challenge to observe experimentally. However, computationally studying the reaction is also challenging because of, inter alia, the Basis Set Incompleteness Error (BSIE). Accordingly, we utilized density functional theory-based calculations and the complete basis set method, to confirm the conformational effect in the neutral hydrolysis of three ethyl acetate analogs: ethyl formate, ethyl acetate, and ethyl fluoroacetate. The results showed that both methods yielded activation energy span, which implies that the conformational effect in the ethyl acetate neutral hydrolysis is not due to the BSIE. The results also demonstrated the importance of polarization and diffuse function in a basis set. The former was to improve the ground state geometry, and the latter was to increase the activation energy.